Rethinking the red scare : the Lusk Committee and New York's crusade against radicalism, 1919-1923 - Pfannestiel, Todd J. (American popular history and culture (Routledge (Firm)), 2003)
Re-evaluates the Red Scare that followed World War One in light of the new methods of political repression developed in New York, methods that established a pattern for future episodes of intolerance.